2005
DOI: 10.2106/jbjs.e.00370
|View full text |Cite
|
Sign up to set email alerts
|

Level of Evidence in Orthopaedic Journals

Abstract: Orthopaedic journals with a higher impact factor are more likely to publish Level-I or II articles. The type and level of information in orthopaedic journals can be reliably classified, and clinical investigators should pursue studies with a higher level of evidence whenever feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(191 citation statements)
references
References 15 publications
10
174
1
6
Order By: Relevance
“…Publications were classified by individuals and institutions, and by publication type (diagnostic, therapeutic, prognostic and economic) and by impact factor (IF) according to Thomson Reuters, using most recent applicable citation index for the period in question [1].…”
Section: Methodsmentioning
confidence: 99%
“…Publications were classified by individuals and institutions, and by publication type (diagnostic, therapeutic, prognostic and economic) and by impact factor (IF) according to Thomson Reuters, using most recent applicable citation index for the period in question [1].…”
Section: Methodsmentioning
confidence: 99%
“…Articles in journals of high scientific quality are good sources for orthopedic surgeons, providing them the evidence they need. It has been reported in the literature that articles having higher level of evidence have been more cited 10 . Even if the articles having higher level of evidence are more convincing in resolving clinical dilemmas, this can not always be achieved 11 .…”
Section: Acta Orthopaedica Et Traumatologica Turcica Is One Of Leadinmentioning
confidence: 99%
“…This 5-level rating system, with Level I evidence being randomized control trials with least bias, allowed for critical appraisal for researchers, editorial reviewers, clinicians, and the public at large regarding the quality rating of scientific articles. Obremskey et al reviewed clinical scientific articles published from January to June 2013 in 9 different orthopedic journals and reported that 11.3 % were Level I, 20.7 % were Level II, 9.9 % were Level III, and 58.1 % were Level IV [34]. The scarcity of higher level of evidence literature is further compounded by a variability of quality between the level I evidence articles.…”
Section: Recommendations Of Bias Classification In Scientific Publicamentioning
confidence: 99%